2017
DOI: 10.1038/s41598-017-04737-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of low birth weight in women with placental malaria associated with P. falciparum VAR2CSA clade

Abstract: Pregnancy associated malaria (PAM) causes adverse pregnancy and birth outcomes owing to Plasmodium falciparum accumulation in the placenta. Placental accumulation is mediated by P. falciparum protein VAR2CSA, a leading PAM-specific vaccine target. The extent of its antigen diversity and impact on clinical outcomes remain poorly understood. Through amplicon deep-sequencing placental malaria samples from women in Malawi and Benin, we assessed sequence diversity of VAR2CSA’s ID1-DBL2x region, containing putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…31 Mother and newborn demographic and clinical data were recorded 31 and are shown in Supplemental P. falciparum samples. The placental samples used in this study have been previously sequenced by Patel et al, 21 (Genbank accession numbers MF061812-MF061963). Perfused placental blood sampling was performed as described elsewhere, with precautions to minimize contamination with peripheral maternal blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Mother and newborn demographic and clinical data were recorded 31 and are shown in Supplemental P. falciparum samples. The placental samples used in this study have been previously sequenced by Patel et al, 21 (Genbank accession numbers MF061812-MF061963). Perfused placental blood sampling was performed as described elsewhere, with precautions to minimize contamination with peripheral maternal blood.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study of placental parasites in Benin, we found 57 distinct placental haplotypes in 56 pregnant women. 21 Furthermore, most women were infected with more than one haplotype, with a mean number of variants per woman of 1.88 (range: 1-7). 21 Given its sequence diversity, the var2csa gene could serve as a marker to distinguish parasite haplotypes in the different compartments in the context of polyclonal infections.…”
Section: Introductionmentioning
confidence: 99%
“…Kazansky et al suggested quill effect arises from pulse front tilt (PFT) of the writing beam [1], which is supported by following works [3][4][5] and is improved by Salter et al by proving that both PFT and time-invariant focal asymmetry may give rise to quill effect [6]. So far all prior works predominately focused on quill effect arising in laser irradiated regions in fused silica that exhibited damage-like textures and were written well above low-loss-waveguide (LLW) writing regime [1][2][3][4][5][6][7][8][9]. In that damage-resulting writing regime and material, quill effect was clearly visible under a transmission mode microscope but this fabrication regime is not particularly useful for function photonic components.…”
mentioning
confidence: 84%
“…Quill effect [1], which manifests as a change in material modification by reversing the writing direction of ultrafast laser direct writing, has been actively studied over the last decade since it was reported by Poumellec et al [2]. Kazansky et al suggested quill effect arises from pulse front tilt (PFT) of the writing beam [1], which is supported by following works [3][4][5] and is improved by Salter et al by proving that both PFT and time-invariant focal asymmetry may give rise to quill effect [6]. So far all prior works predominately focused on quill effect arising in laser irradiated regions in fused silica that exhibited damage-like textures and were written well above low-loss-waveguide (LLW) writing regime [1][2][3][4][5][6][7][8][9].…”
mentioning
confidence: 92%
“…Amplicon analysis in Plasmodium has been adapted to multiple sequencing platforms depending on the desired cost, sample size, and sequence length [3,[9][10][11]. Because of this high resolution and flexibility, amplicon-based methods have been utilized in a range of applications, including studies of allele-specific vaccine efficacy [1], disease severity [10], clearance rate [12], within-host competition [13], relapse rate [9], drug resistance [5][6][7], host selection [8], and population structure [8,14]. Amplicon sequencing has high sensitivity for the detection of minority parasite lineages within an infection, and is of particular interest in longitudinal studies that track intra-host dynamics [3,4].…”
Section: Introductionmentioning
confidence: 99%